2011
DOI: 10.1371/journal.pgen.1002225
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Scant Identifies Endos as a Substrate of Greatwall Kinase and a Negative Regulator of Protein Phosphatase 2A in Mitosis

Abstract: Protein phosphatase 2A (PP2A) plays a major role in dephosphorylating the targets of the major mitotic kinase Cdk1 at mitotic exit, yet how it is regulated in mitotic progression is poorly understood. Here we show that mutations in either the catalytic or regulatory twins/B55 subunit of PP2A act as enhancers of gwlScant, a gain-of-function allele of the Greatwall kinase gene that leads to embryonic lethality in Drosophila when the maternal dosage of the mitotic kinase Polo is reduced. We also show that heteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 35 publications
9
84
0
1
Order By: Relevance
“…This pathway relies on the powerful protein inhibitor of PP2A-B55d, ARPP19, which is activated by its Gwl-dependent phosphorylation. These findings obtained in Xenopus egg extracts (Gharbi-Ayachi et al, 2010;Mochida et al, 2010) were further confirmed by genetic studies in the Drosophila model (Rangone et al, 2011) and highlight the essential role of the Gwl/ARPP19/PP2A module for the maintenance of the mitotic state (Lorca and Castro, 2013). However, the details of the contribution of these molecular players to MPF activation and M-phase entry remain an open and important question.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This pathway relies on the powerful protein inhibitor of PP2A-B55d, ARPP19, which is activated by its Gwl-dependent phosphorylation. These findings obtained in Xenopus egg extracts (Gharbi-Ayachi et al, 2010;Mochida et al, 2010) were further confirmed by genetic studies in the Drosophila model (Rangone et al, 2011) and highlight the essential role of the Gwl/ARPP19/PP2A module for the maintenance of the mitotic state (Lorca and Castro, 2013). However, the details of the contribution of these molecular players to MPF activation and M-phase entry remain an open and important question.…”
Section: Discussionmentioning
confidence: 65%
“…The regulation of PP2A-B55d depends on the kinase Gwl (Castilho et al, 2009;Vigneron et al, 2009). Once activated, Gwl directly phosphorylates two small related proteins, a-endosulfine or ARPP19, both of which then become able to interact with and inhibit PP2A-B55d (Gharbi-Ayachi et al, 2010;Mochida et al, 2010;Rangone et al, 2011). As a consequence, Cdk1 activity is no longer antagonized by PP2A-B55d phosphatase, resulting in an increased and stable level of phosphorylation of the mitotic substrates responsible for cell division (Glover, 2012;Haccard and Jessus, 2011;Lorca and Castro, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work revealed that this attachment requires the cooperation between Drosophila Polo (the founding member of the Plk1 family) and protein phosphatase 2A (PP2A) in association with a B-type regulatory subunit known as Twins [89]. Moreover, Drosophila genetics also revealed an antagonism between Polo/PP2A and the protein kinase Greatwall [89,90]; contributing to the emerging recognition that, in many species, this kinase-phosphatase balance plays a key role in the regulation of the G2/M transition (reviewed in [91][92][93][94]). Although precise mechanistic details of the interactions between these proteins remain to be clarified, the abovementioned studies again highlight the importance of centrosomes and spindle poles for the spatial assembly of regulators of mitotic progression, reminiscent of the situation described in §2 for the fission yeast SPB.…”
Section: (C) Roles Of Centrosomes In Drosophila Developmentmentioning
confidence: 99%
“…Biochemical assays in Xenopus extracts have demonstrated that Greatwall is able to inhibit PP2A-B55 phosphatase complexes by phosphorylating the cAMP-regulated phosphoprotein Arpp19 and α-endosulfine, thus participating in the maintenance of the mitotic state (5)(6)(7)(8). The control of PP2A through the Greatwalldependent phosphorylation of Arpp19/Ensa proteins has also been supported by genetic studies in Drosophila (9,10). The mammalian ortholog of Greatwall, also known as microtubuleassociated serine/threonine kinase-like protein (Mastl), also participates in the maintenance of the mitotic state by inhibiting PP2A phosphatases (11,12).…”
mentioning
confidence: 92%